Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd003774.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral medications for preventing cytomegalovirus disease in solid organ transplant recipients

Abstract: Cochrane Database of Systematic Reviews Main resultsThirty two trials (3737 participants) were identified. Prophylaxis with aciclovir, ganciclovir or valaciclovir compared with placebo or no treatment significantly reduced the risk for CMV disease (19 trials; RR 0.42, 95% CI 0.34 to 0.52), CMV infection (17 trials; RR 0.61, 95% CI 0.48 to 0.77), and all-cause mortality (17 trials; RR 0.63, 95% CI 0.43 to 0.92) primarily due to reduced mortality from CMV disease (seven trials; RR 0.26, 95% CI 0.08 to 0.78). Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(130 citation statements)
references
References 75 publications
2
122
0
6
Order By: Relevance
“…CMV is the most common virus pathogen seen in solid organ transplant patients and symptomatic disease is reported in 30–50% of patients 7. The burden of CMV pneumonia specifically is highest in lung, heart and haematopoietic stem-cell transplantation where it confers significant mortality risks 7–9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMV is the most common virus pathogen seen in solid organ transplant patients and symptomatic disease is reported in 30–50% of patients 7. The burden of CMV pneumonia specifically is highest in lung, heart and haematopoietic stem-cell transplantation where it confers significant mortality risks 7–9.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of CMV pneumonia specifically is highest in lung, heart and haematopoietic stem-cell transplantation where it confers significant mortality risks 7–9. The incidence of CMV pneumonia postlung transplant has been reportedly as high as 50% 7 9…”
Section: Discussionmentioning
confidence: 99%
“…However, prophylactic regimens can protect recipients from certain infections, and the advent of cytomegalovirus (CMV) prophylaxis has greatly reduced the impact of CMV disease on recipient survival [54,55]. A recent, well-conducted, randomized controlled trial of prophylaxis with valganciclovir for at-risk patients (donor or recipient CMV seropositive) showed a marked reduction in CMV disease incidence for a 12-month course of valganciclovir versus a 3-month course [56].…”
Section: Recent Advancesmentioning
confidence: 99%
“…[2728] One analysis found that prophylaxis significantly reduced the rate of graft rejection,[28] but the other did not. [27] Oral valganciclovir and intravenous ganciclovir are equally efficacious in preventing CMV infection and disease. [29] Similarly, oral and intravenous ganciclovir yielded similar results.…”
Section: Cytomegalovirusmentioning
confidence: 99%